Analisis Pengaruh Intensitas Menonton Film Kartun Terhadap Motivasi Belajar Anak Usia Dini - Rahma, Rahma; Halim, Fauziatul; Rafli, Rafli; Kharizmi, Muhammad; Putri, Berliantika (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2024)
This research was done at the kindergarten of Bungong Jeumpa Puteh, Gunci Village, Sawang sub district, Aceh Utara District. It aims to investigate the effect of watching cartoon movie intensity toward the early childhoods’ learning motivation. The research employed the ex post facto method with a descriptive quantitative approach. The sum of the research samples were 25 children, including 15 boys and 10 girls (ages 4-6 years). The data were gotten from questionnaires and documentation, then analyzed quantitatively using formula of the Pearson Product Moment Correlation in order to verify validity and reliability. According to the analysis data, it was discovered that there is a linear and great correlation between the intensity of watching cartoon movies and early childhood learning motivation. The significance score (sig) in Deviation Linearity line was 0.074 is bigger than the value of 0.05 (0.074 > 0.05). besides, the result measurement showed that watching cartoon movie intensity has the significant effect toward the early childhoods’ learning motivation by the F Value measure was 4.429 is bigger than T-Table was 4.26 in significant level 0.046 < 0.05. it could be concluded that the higher Frequency of watching cartoon movie intensity has the effect toward the early childhoods’ learning motivation